PASSWORD ENCRYPTION BASED ON DYNAMIC GRAPH LABELING PRIORITY GENERATION (D.G.L.P.G.) TECHNIQUE - Pal, Sanjay Kumar; Chakraborty, Nupur (Journal of Computer Science and Cybernetics, 2017)
The formalization of speedy technical environment due to the progression in hardware technologies is consistently stimulating the terror of brute force attacks and challenging even the strongest encryption algorithms. Within in this scope the password encryption is severely impacted. In this paper we propose a password encryption technique based on the “Dynamic Graph Labeling Priority Generation (D.G.L.P.G.) Technique” and “Dynamic False Node Insertion (D.F.N.I) Technique”. The emerged technique fits itself in the boundary of the present requisition and is flexible enough to expand its magnitude with the amplifying needs up to the boundary mark of the presented algorithm. The conception originated from the proffered algorithm can be applied to develop ultra advance encryption algorithm.